THE METHOD OF EXPRESSION IN INNATE AND POPULAR IRAQI SCULPTURAL CONTEMPORARY STUDYING BETWEEN (Hadi KadhimNassif) and (Ibrahim al nakash): كفاح عبد المجيد (Al-Academy, 2016)
The innate art,is a major tributary in the art world, It is a bold achievement, has a special flavor, With self-identity, linked to the origins and roots of human ,That goes back to the past and the history and culture of peoples. This business is not limited to only aesthetic side, but is loaded with religious and magical experience, and have social functions, This creations stayed live, breathe, grow, and change with the transformation of society, these processors emerged, from local people have not been trained academically.Their Elvis came from community culture,Which are, Mesopotamian thoroughbreds.This culture that we desperately need today, in order to increase ourselves Iraqi force, In the face of the modern world, which is locked in struggle through "dialogue of civilizations" So this research contains four chapters . the first quarter Interested in the methodological framework of the research, which represents research problem, identifying the following questions: : "What are the methods of expression in Iraqi art innate sculptural contemporary? And What the most important intellectual and environmental references surrounding this art? Using the Iraqis innate sculptors (Hadi Kadhim Nassif) and (Ibrahimal nakash ) as a model for a comparative study between them . The second chapter specialized theoretical framework of the research. The third chapter, represents as the procedures, followed In the analysis of samples according to the context of the theoretical framework in building search tool . So we arrived at a set of key, findings was that the style of the artist (Hadi Kadhim) Differs from the style of the artist (Ibrahim nakash), in terms of idea and content, Despite the similarities between them in dealing with the raw material (wood), but the difference was in the type of organization carved, Between relief sculpture, engineering design style that has characterized the nakash , and the stereo, expressive free design, which has characterized the Hadis done ,The idea, Has required different organizational principles, between completed and another , Therefor , characterize the artist Hadi Kadhim, with his self-expressionist Alsaikologih style, While alnakash used, engineering, and perspective systems , in the embodiment and simulate reality, which was singled out his city, and ideological beliefs .Although the two were creative in drilling technique on wood , and the ability to express through it, but technical Show, between them are different.One of the results of this research, is that there is a difference between innate art which has its roots in primitive art, and folk art, Which has its roots in the local environment, customs , traditions and ideological ideas